MINIMALISASI KESALAHAN SURVEY TOPOGRAFI DALAM PEMETAAN DIGITAL DENGAN KOORDINAT GLOBAL MENGGUNAKAN AUTOCAD LAND DESKTOP DAN GEOGRAPHIC INFORMATION SYSTEM - Lesawengan, Vicky F.; Jansen, Freddy; Manoppo, Fabian J. (JURNAL SIPIL STATIK, 2019)
The development of the era of Globalization and Information Systems are fast, so also developing Satellite Interpretation techniques in digital mapping that is useful to speed up topographic surveys but digital map making must be done in the right way in order to minimize errors in maps used in engineering work planning. This study discusses the use of equipment, measurement methods and correct data processing in accordance with the applicable mapping standards so that it can produce an accurate mapping that matches the actual location conditions.The results obtained: (1) By using measurement techniques and the right equipment, measurement errors can be minimized, from the calculation of Polygon with 66 points, clockwise measurement, Polygon correction is 0 ° 0'02 '' <0 ° 1'24 '', Azimuth Controller error is indicated no more than 5 "in this measurement the obtained error measurement = 0", due to Initial Azimuth and Final Azimuth = 4 ° 49 '42 "closes perfectly thus fulfilling the Geodetic Survey Standard Operating Procedure. (2) From the results of the Ground Survey and Global Positioning System Measurement, the results of the interpolation coordinates are taken to get more precise coordinates in the field. (3) Map depictions with AutoCad Land Development and GIS get Topographic maps with 1 m contour intervals indicating high representation of different locations, this can be achieved by using Ground Survey data and not the results of satelite digitization. (4) The coordinates produced are Global coordinates using the Word Geodetic System 84 navigation satellite system with the Universal Transfer projection model.Keywords: Polygon, Mapping, AutoCad Land Development, GIS